Information and Service Challenges in the 5.0 Industrial Revolution on Student Satisfaction: Empirical Analysis in the Department of Electronics - Muhammad Husin; Ambiyar Ambiyar; Nurhasan Syah (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The industrial revolution 5.0 has had an impact on all education in universities. The spread of the COVID-19 virus has an impact on the education system. These changes affect student satisfaction in taking education.. Universities must improve the quality of information and service quality to achieve student satisfaction. This study aims to analyze the effect of information quality and service quality on student satisfaction. This research includes correlational research. The subjects of this study were 100 students of Informatics Engineering Education. The data analysis technique is regression test. The results showed that (1) the quality of information had a positive and significant effect on student satisfaction (2) the quality of service had a positive and significant effect on student satisfaction (3) the quality of information and the quality of service together had a positive and significant effect on student satisfaction. These findings provide a perception to increase competition towards the industrial revolution 5.0 and the satisfaction of college students must update the quality of information and service quality.